Perennial plants and traditional medicine: Assessing the socio-demographic impacts on traditional remedies. - Xiaonan Wang; Yi Zheng; Xin Cui; Tauseef Anwar; Huma Qureshi; Abdullah (PLoS ONE)
This study assessed the curative uses of wild medicinal plants and investigated the socio-demographic aspects influencing traditional medicinal knowledge in Tehsil Hasilpur, Punjab. Using snowball sampling, data were collected from 300 respondents through interviews and field surveys. Analysis included plant life span, plant parts used, preparation methods, and quantitative indices such as Informant Consensus Factor (ICF), Use Value (UV), and Fidelity Level (FL). The findings revealed that males comprised 85.6% of respondents, reflecting cultural constraints on women's participation. Traditional knowledge was more prevalent among individuals with primary education (53%) and the illiterate (24%). Perennial species dominated (98.6%), leaves are the most commonly utilized plant part (65.33%), and decoctions are the most popular preparation method (24%). High ICF values indicated strong consensus on plant efficacy, with Eucalyptus globulus exhibiting significant use value. These findings emphasize the impact of gender, education, and occupation on knowledge transfer, as well as the ecological significance of local flora. The study recommends integrating traditional medicinal knowledge into healthcare strategies and promoting collaborative conservation efforts to ensure sustainable use of ethnomedicinal resources.